Desain Pembelajaran Operasi Hitung Aljabar Menggunakan Konteks Kuliner Nusantara dengan Teknologi Augmented Reality Berbantuan Android - Pratama, Saputra; Agustiani, Riza (Lentera: Jurnal Ilmiah Kependidikan, 2023)
This study purpose to produce a learning trajectory of arithmetic subtraction operation material for class VII junior high school using the culinary context of the archipelago with augmented reality technology assisted by android. The research method used was design research type validation study. This research using design research method consists of three stages of research. The first stage was preparing for the experiment. The second stage was the experimental design which is divided into two cycles, the first cycle was the pilot experiment and the second cycle was the teaching experiment. The third stage was retrospective analysis which consists of two cycles according to the cycle in the experimental design stage. Learning designs made using augmented reality technology can help and made it easier for students to understand the concept of algebraic subtraction operations in class VII SMP and learning designs that are made can attract students' interested and provided new experiences in carrying out mathematics learning activities, especially algebraic subtraction operations material.